The Position Of The Deed Of Will On Community Property Which Is Made By a Notary - Kurniawati, Baiq Anisha; Djumardin; Wagian, Diangsa (Faculty of Law, University of Mataram, 2025)
This study aims to analyze the validity of a deed of gift that will be executed by a notary without the consent of the married couple, based on Supreme Court Decision Number 2979 K/Pdt/2019. Additionally, it seeks to assess the inadequacy of the responses provided by the Notary Public regarding the deed of gift of will absent the consent of the married couple. The research methodology employed is normative legal research. The findings indicate that the validity of the deed of gift of will contravenes Chapter 36, Paragraph (1) of Law No. 1 of 1974 concerning Marriage, rendering the deed invalid. Furthermore, due to administrative responsibility, the Notary Public may incur liability for deeds executed negligently.